2014
DOI: 10.1590/0100-5405/1970
|View full text |Cite
|
Sign up to set email alerts
|

In vitro sensitivity reduction of Fusarium graminearum to DMI and QoI fungicides

Abstract: Wheat (Triticum aestivum L.) is an important food crop in Brazil, where the annual consumption is currently around 11 million tons, of which 6 million tons are produced and 5.6 million tons are imported (5). Wheat production under prevailing warm and wet weather conditions, as in Southern Brazil, is a difficult task (15).Fungal diseases cause considerable damage to wheat production, particularly those difficult to control, such as fusarium head blight (FHB), caused by Gibberella zeae (Schw.) Petch. (Anamorph F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 15 publications
1
8
1
Order By: Relevance
“…A similar result was found when pyraclostrobin was compared to azoxystrobin against Cercospora spp. isolates, and even when pyraclostrobin was compared to trifloxystrobin against F. graminearum isolates (Avozani et al, 2014;de Mello et al, 2021). For the latter, a recent meta-analysis conducted in Brazil, which compared several DMI + QoI premixes for FHB control, showed that a premix containing azoxystrobin was less effective than one that used pyraclostrobin.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A similar result was found when pyraclostrobin was compared to azoxystrobin against Cercospora spp. isolates, and even when pyraclostrobin was compared to trifloxystrobin against F. graminearum isolates (Avozani et al, 2014;de Mello et al, 2021). For the latter, a recent meta-analysis conducted in Brazil, which compared several DMI + QoI premixes for FHB control, showed that a premix containing azoxystrobin was less effective than one that used pyraclostrobin.…”
Section: Discussionmentioning
confidence: 99%
“…graminearum to this chemical group. To date, only one study has been conducted in the country, which used 10 FGSC strains from Rio Grande do Sul (RS) and Paraná (PR) states to characterize their EC 50 (effective concentration leading to 50% inhibition of conidial germination; Avozani et al, 2014). The objectives of this study were (a) to characterize the sensitivity of F .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…piricola, respectively (Jian-lu et al, 2007). The mean EC 50 of tebuconazole, based on the inhibition of mycelial growth of 10 Fusarium graminearum isolates, was reported to be 0.19 mg/L (Avozani et al, 2014). The EC 50 and EC 90 values for 43% tebuconazole suspension concentrates against Phomopsis asparagi is 7.4241 and 47.1322 mg/L, respectively (Jia et al, 2009).…”
Section: Discussionmentioning
confidence: 99%